Exploring the Relationship between Human Rights and International Relations in The Middle East - Al-Rawashdeh, Dr. Mohammad (Journal of Political Studies, 2025)
Human rights issues in the Middle East are interconnected with the region's international relations, reflecting the unique political systems, cultures, and economies present there. This research aims to analyze the roles of global players and organizations, such as the United Nations and the Arab League, in promoting human rights. The objectives include understanding how these entities have either encouraged or hindered human rights advancements in the region, examining the impact of human rights on foreign policies, and evaluating the effectiveness of diplomatic initiatives and sanctions in addressing civil liberties violations. Given the ongoing conflicts, including the Syrian civil war and the Israeli-Palestinian situation, the research will assess how human rights issues influence international relations. Additionally, it will explore employee rights in Gulf countries and the challenges faced by women and refugees. Using quantitative methods, the study will examine the intersection of diplomacy, sanctions, and global human rights initiatives, seeking to answer how international relations can better address human rights without destabilizing global political systems. Ultimately, the research aims to highlight the significance of human rights in foreign policy and offer recommendations for their integration in the Middle East.